Aesthetic journalism [ how to inform without informing - Cramerotti, Alfredo (Chicago : Intellec, 2009)
Addressing aesthetic journalism, this title investigates why contemporary art exhibitions often consist of interviews, documentaries, and reportage. It traces the shift in the production of truth from